Climate Change Impact Assessment at Watershed Scale - Ahmed, Sadik (My University, 2017)
Climate model projections revealed a likelihood of increased frequency and magnitude of hydrological extremes in future climate due to continued emissions of greenhouse gases. Considering that it will significantly affect the planning and designing of flood management systems, for instance stormwater management infrastructures, and designation of flood risk area, it is vital to investigate the climate change impact on the hydrological processes and respective consequences on the flood management systems. The primary objective of this research is to investigate the climate change impact at watershed scale, and the goal was achieved by investigating the climate change impact on hydrological processes, assessing the potential impact of changed hydrological processes on drainage systems and flooding scenarios. The study area in this research includes Spencer Creek watershed, West Central Mountain drainage area and Clearview Creek drainage area located in Southern Ontario, Canada. The climate projections used in this study were the North American Regional Climate Change Assessment Program (NARCCAP) climate simulations based on SRES A2 scenario. For Spencer Creek watershed, NARCCAP provided eight RCM+GCM pair’s climate projections were bias- corrected, and used as input in a calibrated hydrological model HBV to simulate flows at the outlet of the watershed. A significant improvement of bias-corrected precipitation and temperature was revealed by Brier and Rank Probability Skill Score. The results revealed an increase in winter daily average flows and decrease in other seasons, and approximately 13% increase in annual evapotranspiration, and an increase in high flows and decrease in low flows under future climate conditions. Consequences for changed hydrological processes on urban stormwater management systems were investigated for West Central Mountain drainage area. Design storm depths were calculated by using the best fitted distribution among twenty seven distributions and by applying delta change factor. The PCSWMM model was used for flow simulation and hydraulic analysis for the storm-water management system, specifically storm sewer and detention pond. The assessment results indicate that the performance of the detention pond as well as the storm sewer network will deteriorate under future climate condition as design storm depths increase. For Clearview Creek drainage area, a single event hydrologic model Visual OTTHYMO and hydraulic analysis tool HEC-RAS were used to simulate flow and water level. The results revealed an increase of peak flows ranging from about 26 % to 64% for 2yr and 100yr return periods at the outlet of the Creek, and an average increase of water surface elevation and extents by 30 cm and 37.1 m, respectively, for a 100 year return period flood. Finally, non-stationary frequency analyses for design storm calculation were recommended for more robust and accurate investigation of climate change impact.
Keywords: Climate Change; Storm Water; Watershed; Frequency Analysis; Detention Pond; Storm Sewer; Flood; Hydrology; Hydraulics